Employment status of partnered working women in Australia: examining the impact of male partners' characteristics. - Miranti, R; McNamara, J; Cassells, R (My University, 2014)
Women's participation in the labour market in Australia has increased significantly during the past 20 years. Part of this increase is due to a substantial rise in labour force participation of married women. The theoretical literature has highlighted that the labour supply decision of married women is usually determined in the context of their family labour force participation, particularly the labour supply decision of the husband. This paper examines the effect of the male partner's characteristics on the employment status of women who are either married or living in a de facto relationship. We use data from the Household, Income and Labour Dynamics in Australia survey to understand the nature of these relationships for women engaged in full-time and part-time employment and women who are considered to be underemployed. We find that, when considering other factors that affect employment status, the characteristics of the male partner do have an affect on the employment status of partnered women, however these are complicated and vary with each employed group of women.
Keywords: Families -- Partners; Employment -- Labour force participation; Income & Finance; Employment -- Hours; Beliefs and Values; Employment -- Underemployment; Identity; Income, wealth and finances; Labour market; Employment; Families; Beliefs and Values; Income & Finance; Underemployment; Partners; Labour force participation; Hours; Income, wealth and finances; Identity; Employment and unemployment